An incurable case of love. 6 - Enjoji, Maki (Shojo beat manga., 2021)
"Nurse Nanase has striven to once again meet the prince of her dreams, so how is it he's become such an aggravating doctor?! After witnessing a handsome and charming young doctor save a stranger's life five years ago, Nanase Sakura trained to become a nurse. But when she meets the doctor again and they start working together, she finds Kairi Tendo to be nothing like the man she imagined him to be!... Our Valiant One and the Dark Lord are in mutual lovey-dovey mode! Or so they thought. Now their greatest challenge has arrived! Nanase became a nurse to chase after Dr. Kairi Tendo. Now the two are finally starting to act like lovers. They're busy enjoying blissful days until Kairi's older sister Ryuko goes missing!"--Provided by publisher.